A triacetylandrographolide nanocrystal and its preparation method and application
The preparation of triacetyl-perforated acetonide nanocrystals by high-speed shear antisolvent method and high-pressure homogeneity method solves the problems of low water solubility and poor drug production, significantly improving bioavailability and therapeutic effects for lung injury-related diseases.
Patent Information
- Application Number
- CN202410385289.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-01
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-04-01
AI Technical Summary
The water solubility of triacetyl-peramide lactone is extremely low, resulting in large doses of medication and poor drug production. The existing emulsion preparation methods have problems such as large dosage of auxiliary materials, low drug loading, and poor preparation stability, which cannot effectively improve its bioavailability and its therapeutic effect for lung injury-related diseases.
Triacetyl-perforated lactone nanocrystals were prepared by high-speed shear antisolvent method combined with high-pressure homogenization method, and nanocrystals were obtained by spray drying, and a variety of dosage forms were prepared by adding conventional pharmaceutical excipients to meet the needs of different drug delivery routes.
It significantly improves the dissolution performance and bioavailability of the drug, significantly reduces the dosage used, improves the drug properties, enhances the therapeutic effect on lung injury-related diseases such as COPD, and has a mature and stable preparation process, which is easy to produce and amplify.
Smart Images

Figure CN118236329B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical technology, and in particular relates to triacetylandrographolide nanocrystal and a preparation method and application thereof. Background Art
[0002] Triacetylandrographolide is a derivative obtained by modifying the hydroxyl groups at positions 3, 14, and 19 of andrographolide into esters. It has pharmacological effects such as anti-inflammatory, anti-tumor, neuroprotection, and immunomodulation (Chinese patents ZL 200510017654.6, ZL200710148499.0, ZL200710016490.4, literature Phytotherapy Research, 2023, 37 (2): 410-423, Pharmacological Research, 2019, 144: 227-234, Chinese Journal of Pharmaceutical Sciences, 2017, 52 (9): 738-742, etc.). Studies have found that the absolute bioavailability of triacetylandrographolide is 7.19%, which is more than 7 times higher than that of andrographolide. The pharmacological effect on mice with lung injury-related disease models is significantly improved. However, due to the extremely low water solubility of the drug, there are problems such as large dosage and poor drugability. The example in Chinese patent ZL 200710016490.4 discloses that triacetylandrographolide is prepared into an emulsion to improve its pharmacodynamic effect, but only provides the preparation of the emulsion and the pharmacodynamic evaluation of reducing the TNF-α and IL-1β content in the serum of rabbits with endotoxin shock. No data are provided on improving drug dissolution, increasing bioavailability, and pharmacodynamic treatment of lung injury-related diseases such as acute lung injury and chronic obstructive pulmonary disease. It is impossible to judge the therapeutic effect of triacetylandrographolide for lung injury and the effect of the drug on the pharmacodynamic effect of lung injury-related diseases after being made into an emulsion. At the same time, the emulsion has problems such as large amount of excipients, low drug loading, and poor preparation stability.
[0003] Nanocrystal technology is a formulation technology that directly processes drugs into nanoparticles. Since most drugs retain the crystalline form, they are usually called nanocrystal drugs (referred to as nanocrystals), which can improve the solubility of poorly soluble drugs and the dissolution of their preparations, and improve the bioavailability of drugs. At the same time, compared with traditional nanocarrier-encapsulated drugs such as emulsions, nanocrystals only require a small amount of stabilizer for preparation, and have the advantages of high drug loading, low cost, and easy production and scale-up. At present, there are many nanocrystal drug preparations on the market, such as aprepitant nanocrystal capsules (Emend), megestrol nanocrystal suspension (Megace ES), etc. Chinese patents have disclosed several patents that use nanocrystal technology to improve drug bioavailability (ZL 202211356947.7, ZL202210550188.1, ZL 202111598896.4, etc.).
[0004] Lung injury refers to lung diseases caused by microbial infection of the respiratory tract and lungs or mechanical foreign bodies such as cigarette smoke and haze particles, including acute lung injury and chronic obstructive pulmonary disease, among which COPD is the most common. COPD is a chronic airway disease characterized by airflow limitation, which is not completely reversible and progressive, manifested by complex airway inflammation, oxidative stress, and protease / antiprotease imbalance. As of 2020, COPD has ranked third in the cause of death from diseases worldwide, becoming a major chronic disease "on par" with hypertension and diabetes. The 2018 "China Adult Lung Health Report" shows that the number of COPD patients in my country is close to 100 million, and 1 million patients die each year. At present, the main strategy for the clinical treatment of COPD is the combination of bronchodilators and glucocorticoids, but long-term use of glucocorticoids such as dexamethasone and budesonide has side effects such as suppressing the body's immune function and leading to osteoporosis. The development of new COPD treatment drugs has become a research hotspot.
[0005] Chinese patent ZL 200710016490.4 discloses that triacetylandrographolide is used as an inhibitor of TNF-α and IL-1β for the treatment of COPD. However, the examples only report that triacetylandrographolide can reduce the levels of TNF-α and IL-1β in the supernatant of LPS-induced RAW264.7 cell culture fluid and in the serum of endotoxin shock rabbits, and lack in vitro and in vivo pharmacodynamic data for the treatment of COPD. In addition, COPD is a chronic airway disease characterized by airflow limitation, and improvement of lung function is the key to evaluating the therapeutic effect of drugs. This patent only involves the anti-inflammatory effect of the drug, and lacks the effect of the drug on the pulmonary ventilation function (forced expiratory volume in 0.1 s (FEV10)) of COPD model animals. 0.1 ), forced vital capacity (FVC), 0.1 second rate (FEV 0.1 / FVC), total lung capacity (TLC), functional residual capacity (FRC), airway resistance (RI), dynamic lung compliance (Cydn), etc.), alveolar and airway wall structure, protease level and other indicators. Therefore, it is impossible to judge the therapeutic effect of triacetylandrographolide on COPD. Summary of the invention
[0006] In view of the problems of low water solubility, large dosage and poor drugability of triacetylandrographolide, the present invention proposes a triacetylandrographolide nanocrystal and a preparation method and application thereof, which can effectively increase drug absorption and bioavailability, improve its effect in treating lung injury-related diseases, reduce dosage, improve its drugability, and facilitate preparation processing and application.
[0007] In order to achieve the above object, the technical solution of the present invention is achieved as follows:
[0008] A triacetylandrographolide nanocrystal, which is mainly composed of triacetylandrographolide, a stabilizer and an excipient. The triacetylandrographolide nanocrystal suspension obtained by redissolving in water has an average particle size of drug particles less than 500 nm and a PDI less than 0.2.
[0009] Triacetylandrographolide nanocrystals and triacetylandrographolide raw materials have the same crystal form, and their XRD spectra show obvious crystalline diffraction peaks at 2θ values of 11.71°, 11.83°, 12.38°, 12.50°, 13.46°, 14.37°, 19.63° and 20.48°.
[0010] A triacetylandrographolide nanocrystal preparation comprises the above-mentioned triethylandrographolide nanocrystal and conventional pharmaceutical excipients in the art.
[0011] The triacetylandrographolide nanocrystal preparation includes solid preparation, liquid preparation and semisolid preparation, and the administration routes include oral administration, pulmonary inhalation, injection and local administration.
[0012] Use of the above-mentioned triacetylandrographolide nanocrystals or the above-mentioned triacetylandrographolide nanocrystal preparation in the preparation of drugs for treating lung injury-related diseases.
[0013] The lung injury-related diseases include chronic obstructive pulmonary disease. Triacetylandrographolide nanocrystals or its preparations can significantly improve lung ventilation function, inhibit pathological changes in alveoli and airway walls, and downregulate lung tissue protease levels; they can significantly reduce the number of lung inflammatory cells and the secretion of inflammatory factors, and inhibit the infiltration of inflammatory cells in lung tissue.
[0014] The method for preparing the above-mentioned triacetylandrographolide nanocrystals comprises the following steps:
[0015] (1) dissolving the drug triacetylandrographolide in an organic solvent to obtain a drug solution; dissolving a stabilizer in water to obtain a stabilizer solution;
[0016] (2) adding the drug solution to the stabilizer solution and dispersing the mixture by high-speed shearing to obtain a coarse drug suspension;
[0017] (3) subjecting the crude drug suspension to high-pressure homogenization to obtain a nanocrystalline suspension of triacetylandrographolide;
[0018] (4) adding an excipient to the nanocrystal suspension and preparing triacetylandrographolide nanocrystals by spray drying.
[0019] The organic solvent in step (1) is selected from one or a mixture of ethanol and acetone; the stabilizer is selected from one or more of soybean lecithin, poloxamer 188, hydroxypropyl methylcellulose E5, sodium lauryl sulfate, polyvinyl pyrrolidone K30 and Tween 80; and the excipient in step (4) is one or a mixture of lactose, mannitol and glucose.
[0020] In the step (1), the stabilizer is preferably a mixture of one or both of soybean lecithin and poloxamer 188; and in the step (4), the excipient is preferably a mixture of one or both of lactose and mannitol.
[0021] In the step (1), the mass volume ratio of the drug triacetylandrographolide to the organic solvent is 0.20-0.40 g:1 mL;
[0022] In the step (2), the volume ratio of the drug solution to the stabilizer solution is 1:20 to 1:50, the mass ratio of triacetylandrographolide to the stabilizer in the crude drug suspension is 1:1 to 5:1, and the high-speed shearing conditions are a shear stirring speed of 5000 to 10000 rpm and a shearing time of 5 to 10 min;
[0023] The homogenization pressure of the high pressure homogenization treatment in step (3) is 10,000 to 20,000 psi, and the number of homogenization times is 10 to 20 times;
[0024] In the step (4), the mass volume ratio of the excipient to the triacetylandrographolide nanocrystal suspension is 0.03-0.10 g:1 mL.
[0025] The process parameters for spray drying in step (4) are: inlet temperature 60-70°C, outlet temperature 30-40°C, spray pressure 0.1-0.2 Mpa, injection rate 1.0-2.0 mL / min, and drying air volume 0.5-1.0 m³ / min.
[0026] The present invention has the following beneficial effects:
[0027] (1) A high-speed shear antisolvent method combined with a high-pressure homogenization method was used to prepare a triacetylandrographolide nanocrystal suspension, which was then spray-dried to obtain drug nanocrystals. The obtained nanocrystals can be added with conventional excipients in the field to prepare various dosage forms such as solid preparations, liquid preparations, and semisolid preparations to meet the needs of different routes of administration. Nanocrystals have the advantages of high drug loading, low organic solvent usage, controllable environmental pollution, mature and stable preparation technology, and easy production and scale-up.
[0028] (2) Compared with the raw material drug, triacetylandrographolide nanocrystals can improve the dissolution performance of the drug and significantly increase its bioavailability.
[0029] (3) Compared with the raw material drug, triacetylandrographolide nanocrystals have significant efficacy in treating lung injury-related diseases including COPD, reduce the dosage, facilitate preparation processing, and have good medication compliance and drugability. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 The appearance of the triacetylandrographolide nanocrystal suspension prepared according to Example 1 and the transmission electron microscopy image of the nanocrystals.
[0032] Figure 2 The figure is the powder X-ray diffraction pattern of triacetylandrographolide nanocrystals prepared according to Example 1.
[0033] Figure 3 The in vitro release curves of triacetylandrographolide nanocrystals and the raw material drug prepared in Example 1 in simulated lung fluid.
[0034] Figure 4 The graph is a blood drug concentration-time curve of triacetylandrographolide nanocrystals prepared in Example 1 and the raw drug administered intragastricly to rats.
[0035] Figure 5 This is a graph showing the effect of oral administration of triacetylandrographolide nanocrystals on lung injury in mice with acute lung injury induced by LPS instillation. In the figure, *** is p<0.001, compared with the control group; # is p<0.05, ## is p<0.01, compared with the model group; & is p<0.05, compared with the raw material drug group.
[0036] Figure 6 A graph showing the effect of intragastric administration of triacetylandrographolide nanocrystals on whole blood inflammatory cells and serum inflammatory factors in mice with acute lung injury after LPS instillation was constructed. In the graph, *** is p<0.001, compared with the control group; ### is p<0.001, compared with the model group; & is p<0.05, && is p<0.01, and &&& is p<0.001, compared with the raw material drug group.
[0037] Figure 7This is a graph showing the effect of triacetylandrographolide nanocrystals on inflammatory factors in the supernatant of mouse RAW264.7 cells stimulated by cigarette smoke extract combined with LPS. In the figure, ** is p<0.01, *** is p<0.001, compared with the control group; # is p<0.05, ## is p<0.01, ### is p<0.001, compared with the model group; & is p<0.05, && is p<0.01, &&& is p<0.001, compared with the raw material drug group.
[0038] Figure 8 This is a graph showing the effect of oral administration of triacetylandrographolide nanocrystals on the lung function of COPD mice constructed jointly by cigarette smoke and LPS. In the figure, *** is p<0.001, compared with the control group; ### is p<0.001, compared with the model group; & is p<0.05, &&& is p<0.001, compared with the dexamethasone group, $ is p<0.05, $$$ p<0.001, compared with the raw material drug group.
[0039] Fig. 9 This is a graph showing the effect of oral administration of triacetylandrographolide nanocrystals on lung injury in COPD mice jointly constructed with cigarette smoke and LPS. In the figure, ** is p<0.01, *** is p<0.001, compared with the control group; # is p<0.05, ## is p<0.01, ### is p<0.001, compared with the model group; & is p<0.05, &&& is p<0.001, compared with the raw material drug group.
[0040] Fig.10 This is a diagram showing the effect of oral administration of triacetylandrographolide nanocrystals on inflammatory cells, inflammatory factors and proteases in lung tissue of COPD mice jointly constructed with cigarette smoke and LPS. In the figure, ** is p<0.01, *** is p<0.001, compared with the control group; # is p<0.05, ## is p<0.01, ### is p<0.001, compared with the model group; & is p<0.05, && is p<0.01, &&& is p<0.001, compared with the raw material drug group.
[0041] Fig.11 This is a graph showing the effect of triacetylandrographolide nanocrystal suspension aerosolized pulmonary inhalation on the lung function of mice with COPD jointly constructed with cigarette smoke and LPS. In the figure, * is p<0.05, ** is p<0.01, *** is p<0.001, compared with the control group; # is p<0.05, ## is p<0.01, ### is p<0.001, compared with the model group; & is p<0.05, && is p<0.01, &&& p<0.001, compared with the budesonide group.
[0042] Fig.12This is a graph showing the effect of triacetylandrographolide nanocrystal suspension aerosolized pulmonary inhalation on lung injury in COPD mice jointly constructed with cigarette smoke and LPS. In the figure, *** is p<0.001, compared with the control group; ## is p<0.01, ### is p<0.001, compared with the model group; && is p<0.01, &&& is p<0.001, compared with the budesonide group.
[0043] Fig.13 This is a diagram showing the effects of triacetylandrographolide nanocrystal suspension aerosol pulmonary inhalation on inflammatory cells, inflammatory factors in bronchoalveolar lavage fluid and proteases in lung tissue of COPD mice constructed jointly with cigarette smoke and LPS. In the figure, *** is p<0.001, compared with the control group; # is p<0.05, ## is p<0.01, and ### is p<0.001, compared with the model group; & is p<0.05, && is p<0.01, and &&& is p<0.001, compared with the budesonide group. DETAILED DESCRIPTION
[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Example 1
[0046] This embodiment provides a method for preparing triacetylandrographolide nanocrystals, comprising the following steps:
[0047] Weigh 150 mg of triacetylandrographolide API and dissolve it in 0.5 mL of ethanol to obtain a drug solution. Weigh 75 mg of soybean lecithin and dissolve it in 15 mL of purified water as a stabilizer solution.
[0048] The drug solution was added to the stabilizer solution and dispersed at 5000 rpm for 5 min to obtain a coarse suspension;
[0049] The crude suspension was placed in a high-pressure homogenizer and pre-homogenized at pressures of 3000, 5000, and 7000 psi for 5 cycles, and then the high-pressure homogenization pressure was set to 15000 psi and the homogenization times were 15 times to obtain a nanocrystal suspension;
[0050] Lactose was taken as an excipient and added to the above nanocrystal suspension in a mass volume ratio of 0.1 g:1 mL, and spray drying was performed. The process parameters were: inlet temperature 65°C, outlet temperature 35°C, spray pressure 0.1 Mpa, injection rate 1.0 mL / min, and dry air volume 0.75 m³ / min to obtain triacetylandrographolide nanocrystals; the particle size of the drug particles in the suspension obtained by re-dissolving the nanocrystals with water was 461.6 nm, and the PDI was 0.094.
[0051] Take the obtained nanocrystals and add water to re-dissolve them into a suspension, place them in a transparent vial and take a photo of their appearance (see Figure 1 a), the nanocrystal suspension has a milky white appearance and is evenly dispersed and stable; 10 μL of the above suspension is dripped onto a clean copper mesh covered with a carbon film, excess sample is absorbed with filter paper, and the mesh is left to dry at room temperature. Finally, the dried copper mesh is placed under a transmission electron microscope to observe the morphology of the nanocrystal particles and take pictures (see Figure 1 b) Transmission electron microscopy shows that the nanocrystals are short rods, without aggregation, with a particle size of about 450 nm and a relatively uniform distribution.
[0052] Take triacetylandrographolide nanocrystals (no lactose added during spray drying), triacetylandrographolide API, soybean lecithin, and the physical mixture of triacetylandrographolide and soybean lecithin, and evenly fill them in the grooves of the glass sample plate, and place them on the diffractometer sample stage for scanning. Test conditions: The radiation source is Cu-kα, the tube current is 40 mA, the tube voltage is 40kV, the scanning speed is 2.5° / min, the step length is 0.03°, and the 2θ angle scanning range is 5-60°. Record the XRD diffraction pattern, and judge the crystal form change according to the changes in the diffraction peak position and intensity of each group of samples. The results are shown in Figure 2 .
[0053] like Figure 2 The XRD spectrum showed that soybean lecithin was a diffuse peak without characteristic diffraction peaks; triacetylandrographolide nanocrystals and triacetylandrographolide raw materials showed obvious crystalline diffraction peaks at 2θ values of 11.71°, 11.83°, 12.38°, 12.50°, 13.46°, 14.37°, 19.63°, and 20.48°, indicating that the nanocrystalline drug and the raw material had the same crystal characteristics.
[0054] Example 2
[0055] This embodiment provides a method for preparing triacetylandrographolide nanocrystals, comprising the following steps:
[0056] Weigh 400 mg of triacetylandrographolide API and dissolve it in 1.0 mL of ethanol to obtain a drug solution. Weigh 100 mg of poloxamer 188 and dissolve it in 20 mL of purified water as a stabilizer solution.
[0057] The drug solution was added to the stabilizer solution and high-speed shearing and dispersion was performed at 10,000 rpm for 5 min to prepare a coarse suspension;
[0058] The crude suspension was placed in a high-pressure homogenizer and pre-homogenized at 3000 psi, 5000 psi, and 7000 psi pressures for 5 cycles, and then the high-pressure homogenization pressure was set to 20000 psi and the homogenization times were set to 20 times for high-pressure homogenization to obtain a nanocrystalline suspension;
[0059] Mannitol was added as an excipient to the above nanocrystal suspension in a mass volume ratio of 0.05 g:1 mL, and spray drying was performed. The process parameters were: inlet temperature 65°C, outlet temperature 35°C, spray pressure 0.1 Mpa, injection rate 1.5 mL / min, and dry air volume 1.0 m³ / min to obtain triacetylandrographolide nanocrystals. The particle size of the drug particles in the suspension obtained by adding pure water to the nanocrystals was 436.3 nm, and the PDI was 0.128.
[0060] Example 3
[0061] This embodiment provides a method for preparing triacetylandrographolide nanocrystals, comprising the following steps:
[0062] Weigh 200 mg of triacetylandrographolide API and dissolve it in 0.5 mL of acetone to obtain a drug solution. Weigh 160 mg of soybean lecithin and 40 mg of poloxamer 188 and dissolve them in 20 mL of purified water as a stabilizer solution.
[0063] The drug solution was added to the stabilizer solution and high-speed shearing dispersion was performed at 7500 rpm for 10 min to prepare a coarse suspension;
[0064] The crude suspension was placed in a high-pressure homogenizer and pre-homogenized by cycling at pressures of 3000, 5000, and 7000 psi for 5 times, and then the high-pressure homogenization pressure was set to 15000 psi and the homogenization times were set to 10 times for high-pressure homogenization to obtain a nanocrystalline suspension;
[0065] Lactose and mannitol (both in a mass volume ratio of 0.015 g:1 mL) were added as excipients to the above nanocrystal suspension for spray drying. The process parameters were: inlet temperature 60°C, outlet temperature 40°C, spray pressure 0.2 Mpa, injection rate 2.0 mL / min, and dry air volume 1.0 m³ / min to obtain triacetylandrographolide nanocrystals. The particle size of the drug particles in the suspension obtained by re-dissolving the nanocrystals in water was 445.7 nm, and the PDI was 0.142.
[0066] Example 4
[0067] This embodiment provides a method for preparing triacetylandrographolide nanocrystals, comprising the following steps:
[0068] Weigh 200 mg of triacetylandrographolide API and dissolve it in 1 mL of a mixed solution of ethanol and acetone (volume ratio of 8:1) to obtain a drug solution. Weigh 32 mg of soybean lecithin and 8 mg of Tween 80 and dissolve them in 40 mL of purified water as a stabilizer solution.
[0069] The drug solution was added to the stabilizer solution and dispersed at 5000 rpm for 10 min to obtain a coarse suspension;
[0070] The crude suspension was placed in a high-pressure homogenizer and pre-homogenized at pressures of 3000, 5000, and 7000 psi for 5 cycles, and then the high-pressure homogenization pressure was set to 10000 psi and the homogenization times were set to 20 times for high-pressure homogenization to obtain a nanocrystal suspension;
[0071] A mixture of lactose and mannitol (in a mass volume ratio of 0.04 g:1 mL and 0.01 g:1 mL, respectively) was added as an excipient to the above nanocrystal suspension for spray drying. The process parameters were: inlet temperature 70°C, outlet temperature 30°C, spray pressure 0.2 Mpa, injection rate 2.0 mL / min, and dry air volume 1.0 m³ / min to obtain triacetylandrographolide nanocrystals. The particle size of the drug particles in the suspension obtained by re-dissolving the nanocrystals in water was 485.1 nm, and the PDI was 0.135.
[0072] Example 5
[0073] This embodiment provides a method for preparing triacetylandrographolide nanocrystals, comprising the following steps:
[0074] Weigh 300 mg of triacetylandrographolide API and dissolve it in a mixed solution of 0.75 mL of ethanol and acetone (volume ratio of 1:1) to obtain a drug solution; weigh 100 mg of soybean lecithin and dissolve it in 22.5 mL of purified water as a stabilizer solution;
[0075] The drug solution was added to the stabilizer solution and dispersed at 5000 rpm for 10 min to obtain a coarse suspension;
[0076] The crude suspension was placed in a high-pressure homogenizer and pre-homogenized by cycling for 5 times at pressures of 3000, 5000, and 7000 psi, and then the high-pressure homogenization pressure was set to 20000 psi and the homogenization times were set to 15 times to perform high-pressure homogenization treatment to obtain a nanocrystal suspension;
[0077] Lactose and mannitol (the amount of which was 0.04 g:1 mL and 0.01 g:1 mL, respectively) were weighed as excipients and added to the above nanocrystal suspension for spray drying. The process parameters were: inlet temperature 70°C, outlet temperature 30°C, spray pressure 0.2 Mpa, injection rate 1.0 mL / min, and dry air volume 0.5 m³ / min to obtain triacetylandrographolide nanocrystals. The particle size of the drug particles in the suspension obtained by re-dissolving the nanocrystals in water was 460.9 nm, and the PDI was 0.130.
[0078] Example 6
[0079] This embodiment provides a method for preparing triacetylandrographolide nanocrystals, comprising the following steps:
[0080] Weigh 240 mg of triacetylandrographolide API and dissolve it in 1.0 mL of ethanol to obtain a drug solution. Weigh 120 mg of stabilizer (soy lecithin and poloxamer 188 in a mass ratio of 2:1) and dissolve it in 40 mL of purified water as a stabilizer solution.
[0081] The drug solution was added to the stabilizer solution and high-speed shearing dispersion was performed at 7000 rpm for 8 min to prepare a coarse suspension;
[0082] The crude suspension was placed in a high-pressure homogenizer and pre-homogenized by cycling for 5 times at pressures of 3000, 5000, and 7000 psi, and then the high-pressure homogenization pressure was set to 20000 psi and the homogenization times were set to 15 times to perform high-pressure homogenization treatment to obtain a nanocrystal suspension;
[0083] Lactose (mass volume ratio 0.03 g:1 mL) was added as an excipient to the above nanocrystal suspension for spray drying. The process parameters were: inlet temperature 65°C, outlet temperature 35°C, spray pressure 0.1 Mpa, injection rate 1.0 mL / min, and dry air volume 0.75 m³ / min to obtain triacetylandrographolide nanocrystals. The particle size of the drug particles in the suspension obtained by re-dissolving the nanocrystals in water was 417.5 nm, and the PDI was 0.118.
[0084] Application Example 1
[0085] Preparation of triacetylandrographolide nanocrystal dry suspension
[0086] Take 2.0 g of triacetylandrographolide nanocrystals obtained in Example 1, add 0.05 g of sodium carboxymethyl cellulose, and mix thoroughly to obtain triacetylandrographolide nanocrystal dry suspension. The nanocrystal dry suspension can be evenly dispersed by adding water, and no obvious sedimentation layer is formed when it is left to stand for 30 minutes.
[0087] Application Example 2
[0088] Preparation of triacetylandrographolide nanocrystalline dispersible tablets
[0089] Take 2.0 g of triacetyl andrographolide nanocrystals obtained in Example 1, add 0.14 g of sodium carboxymethyl starch and 0.06 g of micro-powder silica gel, mix well, and use a 9 mm shallow arc die to press the tablets, with a tablet weight of 250 mg. The surface of the nanocrystalline dispersible tablet is smooth and complete, and in the dispersion uniformity test, the dispersible tablet can be completely disintegrated and passed through the sieve within 1 min.
[0090] Experimental Example 1: Determination of the in vitro release of triacetylandrographolide nanocrystals in simulated lungs
[0091] The triacetylandrographolide nanocrystals prepared in Example 1 were used as the experimental object. An activated dialysis bag with a molecular weight cutoff of 8000-14000 Da was taken, and 5 mL of simulated lung fluid was added thereto. Triacetylandrographolide nanocrystals (0.5 mg in terms of triacetylandrographolide) were accurately weighed and dispersed and suspended in the above-mentioned simulated lung fluid. Both ends were tied tightly, and then put into a conical flask containing 100 mL of simulated lung fluid in vitro release medium (medium composition is shown in Table 1). The conical flask was placed in a constant temperature air bath oscillator (37° C., 120 r / min). At different time points (0.5 h, 1 h, 2 h, 4 h, 6 h, 8 h, 12 h, 24 h, 36 h and 48 h), 2 mL of the release solution was taken and filtered through a 0.22 μm filter membrane. The filtrate was taken and the drug concentration was determined by HPLC. At the same time, 2 mL of isothermal simulated lung fluid was added to the release medium. The cumulative release percentage is calculated based on the measurement results, and the release curve of the nanocrystals is plotted. At the same time, an amount of triacetylandrographolide API equal to that of the nanocrystals used for the above release measurement is taken, and the same method as the nanocrystal release measurement method is used to plot the release curve of the API.
[0092] The above method was used to conduct experiments on raw materials with the same effective content.
[0093] Table 1 Composition of simulated lung fluid in vitro release medium
[0094]
[0095] Results Figure 3 Compared with the raw material, the in vitro release rate of triacetylandrographolide nanocrystals was significantly accelerated, with the cumulative release percentage increasing from 39% to 64% at 12 h and from 42% to 69% within 48 h.
[0096] Experimental Example 2: Determination of the bioavailability of triacetylandrographolide nanocrystals administered orally to rats
[0097] The triacetylandrographolide nanocrystals obtained in Example 1 were used as test subjects, with a total of 12 SD rats (half male and half female, 200±20 g).
[0098] Before the experiment, they were randomly divided into two groups (n=6, half male and half female) according to body weight. The experiment was carried out after fasting for 12 hours but not water. One group was gavaged with triacetylandrographolide bulk drug suspension (dose of 200 mg / kg), and the other group was gavaged with triacetylandrographolide nanocrystal suspension (calculated as triacetylandrographolide, 50 mg / kg).
[0099] Before administration, blank blood was collected. At the specified time (0.083 h, 0.25 h, 0.50 h, 0.75 h, 1 h, 2 h, 4 h, 6 h, 7 h, 8 h, 10 h, 12 h, and 24 h), 200 μL of blood was collected from the venous plexus of the retina and placed in a heparinized blood collection tube. The blood samples were centrifuged at 5000 rpm for 10 min, and plasma samples were collected. The drug concentration in the plasma samples was determined after treatment, and the blood drug concentration-time curve was drawn. The relevant pharmacokinetic parameters, including AUC, were calculated according to the non-compartmental model using WinNonlin® 6.4 version (Pharsight Corporation, USA) software. 0-t 、MRT、CL、Vd、C max 、T max , the results are shown in Figure 4 and Table 2.
[0100] Taking the API as reference, the relative bioavailability of triacetylandrographolide nanocrystals was calculated according to the following formula:
[0101]
[0102] Where AUC 0-t,纳米晶 , AUC 0-t,原料药 The areas under the drug-time curves at time 0-t correspond to triacetylandrographolide nanocrystals and original drug, respectively;
[0103] Dose 原料药 、Dose 纳米晶 They correspond to the oral administration doses of triacetylandrographolide raw material and nanocrystals respectively.
[0104] Table 2 Pharmacokinetic parameters of triacetylandrographolide nanocrystals and raw materials administered orally to rats
[0105]
[0106] MRT (0-t) It is the average residence time of drug molecules in the body, indicating the time required to eliminate 63.2% of the drug from the body;
[0107] T 1 / 2 The terminal elimination half-life is the time required for the blood drug concentration in the terminal phase to decrease by half;
[0108] T max The time required to reach the peak concentration of the drug after administration. This parameter reflects the speed at which the drug enters the body. The faster the absorption rate, the shorter the peak time;
[0109] C max Peak drug concentration refers to the highest blood drug concentration after administration. This parameter is an important indicator of the absorption rate and degree of the drug in the body.
[0110] V d It is the proportional constant between the amount of drug in the body and the blood concentration when the drug reaches dynamic equilibrium in the body. The unit is generally L. This parameter reflects the degree of distribution of the drug in the body. The higher the value, the wider the distribution. The apparent distribution volume is numerically obtained by the ratio of the clearance rate to the terminal elimination rate;
[0111] F is bioavailability, a measure of the speed and extent to which a drug is absorbed into the blood circulation, and is an important indicator for evaluating the degree of drug absorption. Bioavailability can be divided into absolute bioavailability and relative bioavailability. The former is used to compare the absorption differences between two routes of administration, and the latter is used to evaluate the absorption differences between two preparations.
[0112] CL is the clearance rate, which is the apparent distribution volume of the drug cleared from the body per unit time. The unit is generally L / h. This parameter is an important parameter that reflects the body's characteristics of drug disposal and is closely related to physiological factors. The clearance rate is obtained based on the ratio of dose to AUC (0-∞).
[0113] Depend on Figure 4 It can be seen that nanocrystals can significantly improve the oral bioavailability of triacetylandrographolide in rats by oral gavage. Compared with the raw material, the oral relative bioavailability of triacetylandrographolide nanocrystals is 421%.
[0114] Experimental Example 3: Evaluation of the efficacy of intragastric administration of triacetylandrographolide nanocrystals in treating the acute lung injury mouse model established by LPS instillation
[0115] Triacetylandrographolide nanocrystal dry suspension was prepared according to Application Example 1, and 70 male KM mice (20±2 g) were selected for the experiment.
[0116] Before the experiment, the mice were randomly divided into 7 groups (n=10) according to their body weight, including control group, model group, dexamethasone group (1 mg / kg), raw material drug group (200 mg / kg), and nanocrystal group (50, 100, and 200 mg / kg in terms of triacetylandrographolide).
[0117] On the first day, LPS solution (5 mg / kg) was instilled into the trachea of mice in the model group and the treatment group, and the corresponding volume of normal saline was instilled into the trachea of mice in the control group. The treatment group was gavaged from the second day to the sixth day, once a day, and the control group and the model group were gavaged with the corresponding volume of 0.5% CMC-Na (0.1 mL / g). The experiment was terminated on the seventh day, and the eyeballs of the mice were removed to collect blood. 10 μL was taken for the complete blood cell count of the mice, and the rest of the blood was used to prepare serum and detect the level of inflammatory factors by ELISA. After blood sampling, the mice were killed and the lungs were removed, weighed and the lung index was calculated; the left lung was weighed to obtain the wet weight of the left lung, which was placed in a 1.5 mL centrifuge tube that had been dried to a constant weight in advance, placed in a 60°C oven for forced air drying for 72 h, and the total weight of the centrifuge tube and the lung dry weight was weighed to calculate the wet / dry weight ratio of the mouse left lung; the right lower lobe of the mouse lung was taken, immersed in 4% paraformaldehyde and fixed for 24 h, and dehydrated, paraffin-embedded, sectioned (5 μm), HE stained, and sealed using conventional methods to prepare paraffin sections of mouse lung tissue, and the pathological changes of mouse lung tissue were observed and photographed.
[0118] The results showed that nanocrystals (50, 100, 200 mg / kg) significantly reduced the lung index and lung wet / dry weight ratio of mice with acute lung injury (see Figure 5 a); significantly alleviated the symptoms of lung injury such as alveolar wall edema, alveolar septum thickening, and inflammatory cell infiltration in mice induced by lipopolysaccharide (results see Figure 5 b). Among them, the protective effect of low-dose nanocrystals on lung injury in mice was comparable to that of the API (200 mg / kg), and the effect of the same dose of nanocrystals was superior to that of the original drug. Nanocrystals (50, 100, 200 mg / kg) significantly inhibited the systemic inflammatory response of mice induced by lipopolysaccharide, as shown by a significant decrease in the total cell count, lymphocyte count, neutrophil count in the whole blood of mice and the levels of TNF-α, IL-6, and IL-1β in the serum; except for IL-1β, the effects of each dose of nanocrystals on the above indicators were significantly superior to those of the API (results in Figure 6 ), nanocrystals have an effect comparable to dexamethasone.
[0119] Experimental Example 4: Evaluation of the efficacy of triacetylandrographolide nanocrystals in inhibiting the secretion of inflammatory factors by mouse macrophages RAW264.7 stimulated by cigarette smoke extract combined with LPS
[0120] RAW264.7 cells in the logarithmic growth phase were taken and inoculated in 6-well plates for overnight culture. They were divided into control group, model group, raw material drug group (3 μM), and nanocrystal group (1, 2, and 3 μM in terms of triacetylandrographolide). After adding the corresponding drugs or solvents, they were placed in an incubator for 1 h. The supernatant was discarded, and the culture medium containing a final concentration of 0.0625% cigarette smoke extract, 3 μg / mL LPS and the corresponding dose of drugs or solvents was added, and the cells were placed in an incubator for further culture for 24 h. The culture medium in the 6-well plate was centrifuged at 12000 g for 5 min, and the supernatant was taken, and the level of inflammatory factors was detected by ELISA.
[0121] The results showed that triacetylandrographolide nanocrystals (1, 2, 3 μM) could significantly inhibit the high secretion of TNF-α and IL-6 in RAW264.7 cells induced by cigarette smoke extract combined with LPS; the effect of low-dose nanocrystals was equivalent to that of the API (3 μM), and the effect of the same dose of nanocrystals was better than that of the API ( Figure 7 ).
[0122] Experimental Example 5: Evaluation of the efficacy of oral administration of triacetylandrographolide nanocrystals combined with cigarette smoke fumigation and LPS instillation in a mouse model of chronic obstructive pulmonary disease
[0123] The drug used was the triacetylandrographolide nanocrystal dry suspension obtained in Application Example 1, and male KM mice were selected for the experiment, with a total of 105 mice (20±2 g). Before the start of the experiment, they were randomly divided into a control group, a model group, a dexamethasone group (1 mg / kg), a raw material group (200 mg / kg), and a nanocrystal group (50, 100, and 200 mg / kg in terms of triacetylandrographolide), with a total of 7 groups (n=15).
[0124] From day 1 to day 90, the animals were placed in an animal gas fumigation chamber and the total particle concentration of cigarette smoke was maintained at 500 mg / m 3 , smoke once a day, once every 1 hour, 6 days a week.
[0125] The model animals were sprayed with 50 μL of LPS solution (20 μg / mL) into the lungs on day 91;
[0126] The drug-treated group was intragastrically administered once a day from day 92 to day 96, and the mice in the control group and model group were intragastrically administered with the corresponding volume of 0.5% CMC-Na (0.1 mL / g).
[0127] The experiment was terminated on day 97, and the trachea was intubated and connected to the mouse plethysmography chamber to measure FEV 0.1 , FVC, FEV 0.1 / FVC, TLC, FRC, RI, Cydn and other lung function indicators. Then, the chest cavity was opened, the right hilum was ligated to lavage the left lung, and the bronchial lavage fluid was collected. The number of inflammatory cells and the level of inflammatory factors were detected by Giemsa staining and ELISA, respectively. The right lung was weighed and the mouse lung index was calculated; the right lower lobe was taken, and paraffin sections of mouse lung tissue were made in the same way as in Experimental Example 3, and the pathological changes of mouse lung tissue were observed and photographed; the remaining lung tissue was stored at -80 ° C, and the levels of MMP-9 and NE were detected by ELISA.
[0128] The results showed that nanocrystals (100, 200 mg / kg) significantly increased FVC and FEV 0.1 / FVC, Cydn, reduced TLC, FRC, RI, and improved ventilation function in COPD mice (results in Figure 8 Except for Cydn, 50 mg / kg nanocrystals can significantly improve the above indicators, and the effect is equivalent to that of the raw material drug (200 mg / kg) (see the results Figure 8 ). For FVC, FEV 0.1 / FVC, Cydn and RI, the effect of nanocrystals at the same dose was better than that of the API. Nanocrystals (50, 100, 200 mg / kg) significantly reduced the lung index of COPD mice, and the effect of nanocrystals at each dose was significantly better than that of the API; it significantly alleviated the lung injury symptoms of COPD mice, such as alveolar wall destruction and fusion, bronchial wall thickening and inflammatory cell infiltration (results see Fig. 9 ). Nanocrystals (50, 100, 200 mg / kg) significantly inhibited the pulmonary inflammatory response of COPD mice, as shown by a significant decrease in the total cell count, macrophage count, lymphocyte count, neutrophil count, and TNF-α, IL-6, and IL-1β levels in the bronchial lavage fluid of mice; among them, the effect of low-dose nanocrystals was equivalent to that of the raw material drug, and the effect of the same dose of nanocrystals was better than that of the raw material drug (results see Fig.10 ). Nanocrystals (50, 100, 200 mg / kg) significantly inhibited the levels of MMP-9 and NE in the lung tissue of COPD mice, and the effects of nanocrystals at each dose were significantly better than those of the raw drug (see the results). Fig.10 c) Nanocrystals have an effect comparable to that of dexamethasone.
[0129] Experimental Example 6: Evaluation of the efficacy of triacetylandrographolide nanocrystal suspension aerosol inhalation combined with cigarette smoke fumigation and LPS instillation in the establishment of a mouse model of chronic obstructive pulmonary disease
[0130] The drug used was the triacetylandrographolide nanocrystal dry suspension obtained in Application Example 1, and male KM mice were selected for the experiment, with a total of 75 mice (20±2 g). Before the experiment, they were randomly divided into a control group, a model group, a budesonide group (0.5 mg / kg), and a nanocrystal low-dose and high-dose administration group (based on the effective content of triacetylandrographolide of 10 and 20 mg / kg), with a total of 5 groups (n=15).
[0131] According to Experimental Example 5, a COPD mouse model was constructed, and the mice were administered with drugs in the lungs from day 92 to day 96, once every other day; the control group and the model group were given the same volume of normal saline. On day 97, the lung function index, lung index, alveolar lavage fluid inflammatory cell count and inflammatory factors, protease level detection, and lung tissue section preparation and observation of the mice were all carried out according to Experimental Example 5.
[0132] The results showed that nanocrystals (20 mg / kg) significantly increased FVC and FEV 0.1 / FVC, Cydn, reduced TLC, FRC, RI, and improved ventilation function in COPD mice (results in Fig.11 ). Except for Cydn, 10 mg / kg nanocrystals can improve the above indicators. Nanocrystals (10, 20 mg / kg) significantly reduced the lung index, alveolar mean intercept, mean alveolar area and lung inflammation index of COPD mice (results see Fig.12 Nanocrystals (10, 20 mg / kg) significantly inhibited the pulmonary inflammatory response in COPD mice, as shown by a significant decrease in the total cell count, macrophage count, lymphocyte count, neutrophil count, and TNF-α, IL-6, and IL-1β levels in the bronchial lavage fluid of mice (see results). Fig.13 a, b). At the same time, nanocrystals (10, 20 mg / kg) significantly inhibited the levels of MMP-9 and NE in the lung tissues of COPD mice (see results). Fig.13 c). Low-dose nanocrystals have the same effect as budesonide; except for TLC, high-dose nanocrystals are superior to budesonide in the above indicators.
[0133] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A triacetylandrographolide nanocrystal, characterized in that: The triacetylandrographolide nanocrystals are mainly composed of triacetylandrographolide, a stabilizer and an excipient. The average particle size of the drug particles in the triacetylandrographolide nanocrystal suspension obtained by re-dissolving in water is less than 500 nm, and the PDI is less than 0.2; the triacetylandrographolide nanocrystals are prepared by a high-speed shear anti-solvent method combined with a high-pressure homogenization method to prepare the triacetylandrographolide nanocrystal suspension, and the nanocrystals are further prepared by spray drying; the stabilizer is a mixture of one or both of soybean lecithin and poloxamer 188, or a mixture of soybean lecithin and Tween 80; the excipient is a mixture of one or both of lactose and mannitol.
2. The triacetylandrographolide nanocrystal according to claim 1, characterized in that: The triacetylandrographolide nanocrystals and the triacetylandrographolide raw material have the same crystal form, and the XRD spectra of the two have obvious crystal diffraction peaks at 2θ values of 11.71°, 11.83°, 12.38°, 12.50°, 13.46°, 14.37°, 19.63° and 20.48°.
3. A triacetylandrographolide nanocrystal preparation, characterized in that: The invention comprises the triethylandrographolide nanocrystals as described in claim 1 or 2 and conventional pharmaceutical excipients in the art.
4. The triacetylandrographolide nanocrystalline preparation according to claim 3, characterized in that: The triacetylandrographolide nanocrystal preparation includes solid preparation, liquid preparation and semisolid preparation, and the administration routes include oral administration, pulmonary inhalation, injection and local administration.
5. Use of the triacetylandrographolide nanocrystals according to claim 1 or 2 or the triacetylandrographolide nanocrystal preparation according to claim 3 or 4 in the preparation of drugs for treating lung injury-related diseases; the lung injury-related diseases are acute lung injury or chronic obstructive pulmonary disease.
6. The method for preparing triacetylandrographolide nanocrystals according to claim 1 or 2, characterized in that: The steps include: (1) dissolving the drug triacetylandrographolide in an organic solvent to obtain a drug solution; dissolving a stabilizer in water to obtain a stabilizer solution; (2) adding the drug solution to the stabilizer solution and dispersing the mixture by high-speed shearing to obtain a coarse drug suspension; (3) subjecting the crude drug suspension to high-pressure homogenization to obtain a nanocrystalline suspension of triacetylandrographolide; (4) adding an excipient to the nanocrystal suspension and preparing triacetylandrographolide nanocrystals by spray drying.
7. The method for preparing triacetylandrographolide nanocrystals according to claim 6, characterized in that: The organic solvent in step (1) is selected from ethanol and acetone or a mixture of the two.
8. The method for preparing triacetylandrographolide nanocrystals according to claim 7, characterized in that: In the step (1), the mass volume ratio of the drug triacetylandrographolide to the organic solvent is 0.20-0.40 g:1 mL; In the step (2), the volume ratio of the drug solution to the stabilizer solution is 1:20 to 1:50, the mass ratio of triacetylandrographolide to the stabilizer in the crude drug suspension is 1:1 to 5:1, and the high-speed shearing conditions are a shear stirring speed of 5000 to 10000 rpm and a shearing time of 5 to 10 min; The homogenization pressure of the high pressure homogenization treatment in step (3) is 10,000 to 20,000 psi, and the number of homogenization times is 10 to 20 times; In the step (4), the mass volume ratio of the excipient to the triacetylandrographolide nanocrystal suspension is 0.03-0.10 g:1 mL.
9. The method for preparing triacetylandrographolide nanocrystals according to claim 8, characterized in that: The process parameters for spray drying in step (4) are: inlet temperature 60-70°C, outlet temperature 30-40°C, spray pressure 0.1-0.2Mpa, injection rate 1.0-2.0 mL / min, and drying air volume 0.5-1.0 m³ / min.
Citation Information
Patent Citations
Pharmaceutical composition containing triacetyl andrographolidume and medical use of the same
CN101129354A
Albendazole nanosuspension with relatively high bioavailability and preparation method of albendazole nanosuspension
CN114224834A
Improved abiraterone acetate nanocrystal oral preparation and preparation method thereof
CN114948885A
Hyaluronidase-stabilized Brinolon nanocrystals, their preparation methods and applications
CN115957332B
Compsn. of medication of containing creat lactone of triacetyl and usages
CN1695612A